Histone deacetylase 6 inhibitor tubastatin A attenuates angiotensin II-induced hypertension by preventing cystathionine γ-lyase protein degradation. (August 2019) - Chi, Zhexi; Byeon, Hye-Eun; Seo, Eunjeong; Nguyen, Quynh-Anh T.; Lee, Wonbeom; Jeong, Yunyong; Choi, Juyong; Pandey, Deepesh; Berkowitz, Dan E.; Kim, Jae Hyung; Lee, Sang Yoon
Graphical abstract: Abstract: Cystathionine γ-lyase (CSEγ) is a hydrogen sulfide (H2 S)-producing enzyme. Endothelial H2 S production can mediate vasodilatory effects, contributing to the alleviation of hypertension (high blood pressure). Recent studies have suggested a role of histone deacetylase 6 (HDAC6) in hypertension, although its underlying mechanisms are poorly understood. Here, we addressed the potential regulation of CSEγ by HDAC6 in angiotensin II (AngII)-induced hypertension and its molecular details focusing on CSEγ posttranslational modification. Treatment of mice with a selective HDAC6 inhibitor tubastatin A (TubA) alleviated high blood pressure and vasoconstriction induced by AngII. Cotreatment of the aorta and human aortic endothelial cells with TubA recovered AngII-mediated decreased H2 S levels. AngII treatment upregulated HDAC6 mRNA and protein expression, but conversely downregulated CSEγ protein. Notably, potent HDAC6 inhibitors and HDAC6 siRNA as well as a proteasomal inhibitor increased CSEγ protein levels and blocked the downregulatory effect of AngII on CSEγ. In contrast, other HDAC isoforms-specific inhibitors and siRNAs did not show such blocking effects. Transfected CSEγ protein levels were also reciprocally regulated by AngII and TubA, and were reduced by wild-type, but not by deacetylase-deficient, HDAC6. Moreover, TubA significantly increased both protein stability and K73 acetylation level of CSEγ. Consistent with these results, AngII induced CSEγ ubiquitination and degradation, which was inhibited by TubA. Our results indicate that AngII promoted HDAC6-dependent deacetylation of CSEγ at K73 residue, leading to its ubiquitin-mediated proteolysis, which underlies AngII-induced hypertension. Overall, this study suggests that upregulation of CSEγ and H2 S through HDAC6 inhibition may be considered as a valid strategy for preventing the progression of hypertension.